PRE-EMERGENCE SEED TREATMENTS BASED ON SILICA AND METHYLENE BLUE - Krupska, T.V.; Holovan, A.P.; Siora, I.V.; Тurov V.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
Samples of composite materials based on silica (hydrophilic and hydrophobic), their mixture and methylene blue (1, 2, 4, 8 wt. %) as fungicide were created and applied directly to the surface of wheat seeds by spraying before sowing. The energetic and fungicidal properties of the composites were studied. It was found that by the method of mechanochemical treatment of silica with methylene blue it is possible to create effective fungicide composites for pre-sowing treatment of seeds of grain crops, which at the same time significantly increase the germination of plants. Composites based on hydrophobic silica are characterized by long-term desorption of methylene blue, which possibly increases their fungicidal properties.